DEVELOPMENT OF AN INTEGRATED E-BOOKLET I-SETS (ISLAMIC, SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) ENVIRONMENTAL CHANGE MATERIAL FOR CLASS X SMA/MA STUDENTS - Nana Roisatulkusna; Nasrul Hakim (Universitas Lambung Mangkurat, 2024)
The use of integrated I-SETS (Islamic, Science, Environment, Technology, and Society) learning media on environmental change aims to train students' creativity. This research aims to analyze the feasibility, student responses and teacher responses to the product being developed, namely the I-SETS integrated e-booklet on environmental change. The research carried out is research and development (R&D), using the ADDIE development model. Data collection techniques used were interviews and questionnaires (validation, teacher and student responses). The test subjects were carried out on one teacher and 11 class XI students of SMA Negeri 1 Kotagajah. Data analysis in this research used qualitative and quantitative data. The research results indicate that the media developed has met the following criteria: (1) material expert validation of 74% with